H. Bergson on the Problem of Origin of Life - Bartusiak, Pavlo (Problemos, 2024)
Henri Bergson’s conjectures about the origin of life avoid providing a solution to the problem, and yet he did make some suggestions. A close reading of his texts reveals the philosopher’s implicit assumption of an origin of life on Earth through natural processes. This paper is concerned with the concept of an élan, and focuses on the evolution of this philosophical concept in Bergson’s thought. The argument divides the élan from its constant companion, vital, in order to highlight its non-spiritual aspect which applies to what that Bergson described as “physiological life.” I emphasize that élan has a history, and that there must have been a moment when an élan began. Finally, the argument moves from élan’s history/origin to life’s history/origin.
Keywords: Bergson; origin of life; physiological life; élan; élan vital